2014
DOI: 10.1007/s10886-014-0519-9
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness of Harlequin Bug, Murgantia histrionica, Aggregation Pheromone: Field Response to Isomers, Ratios, and Dose

Abstract: A two-component pheromone, (3S,6S,7R,10S)- and (3S,6S,7R,10R)-10,11-epoxy-1-bisabolen-3-ol (murgantiol), present in emissions from adult male harlequin bugs, Murgantia histrionica, is most attractive in field bioassays to adults and nymphs in the naturally occurring ratio of ca. 1.4:1. Each of the two individual synthetic stereoisomers is highly attractive to male and female adults and nymphs, but is more attractive in combination and when deployed with a harlequin bug host plant. Blends of 8 stereoisomers als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Moreover, in other pentatomid bugs, male-produced compounds act as sex pheromones attracting only females, such as in Piezodorus guildinii (Westwood) [32], T. pallidovirens [33], Oebalus poecilus (Dallas) [34], Eysarcoris parvus (Uhler) [35], and Pallantia macunaima (Grazia) [36]. In other cases, the male-produced compounds act as aggregation pheromones, attracting females, males, and even nymphs, such as in Murgantia histrionica (Hahn) [37,38], N. viridula [27], Eysarcoris lewisi (Distant) [39], Euschistus tristigmus (Say) [18,30], and H. halys [40].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in other pentatomid bugs, male-produced compounds act as sex pheromones attracting only females, such as in Piezodorus guildinii (Westwood) [32], T. pallidovirens [33], Oebalus poecilus (Dallas) [34], Eysarcoris parvus (Uhler) [35], and Pallantia macunaima (Grazia) [36]. In other cases, the male-produced compounds act as aggregation pheromones, attracting females, males, and even nymphs, such as in Murgantia histrionica (Hahn) [37,38], N. viridula [27], Eysarcoris lewisi (Distant) [39], Euschistus tristigmus (Say) [18,30], and H. halys [40].…”
Section: Discussionmentioning
confidence: 99%
“…This implicates natural synergistic cues present in a fruiting host plant, such as constitutive plant volatiles from the leaves or fruit (Piñero and Prokopy 2003) or visual cues. Other stink bugs, for example M. histrionica, use natural cues (semiochemicals) emitted by their host plants (e.g., collards in this case), as traps baited with the species' aggregation pheromone are much more attractive when coupled with the host plant (Weber et al 2014b). In Rhyzopertha dominica (F.) (Coleoptera: Bostrichidae), the presence of maize host odors enhances the response of conspecifics to male-produced aggregation pheromone (Bashir et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Khrimian et al [13] showed that the pheromone consisted of two stereoisomers, (3 S ,6 S ,7 R ,10 S )- and (3 S ,6 S ,7 R ,10 R )-10,11-epoxy-1-bisabolen-3-ol, which occur in a ~1.4:1 ratio in emissions of adult male harlequin bug. Weber et al [14] demonstrated that, in the field, lures containing a synthetic eight-stereoisomer blend were of comparable attractiveness with pure pheromone components to both sexes in adults, as well as to nymphs, and that presence of a host plant (collard) increased this attractiveness. Cabrera Walsh et al [15] found that, although harlequin bugs were strongly attracted to host plants by their pheromone lure, they were not retained more on plants with pheromone than those without it, an important consideration for trap cropping and pesticide application strategies.…”
Section: Introductionmentioning
confidence: 99%